An analysis of English writing errors of Kurdish EFL post-graduate students - Ali, Idrees (Humanities Journal of University of Zakho, 2024)
This study aims to recognize, categorize, and assess the errors in English writing done by Kurdish post-graduate learners enrolled at Language Center (LC) of the University of Zakho, Kurdistan Region of Iraq. This is conducted via applying the error analysis technique, which is considered a vital part of EFL research. By using a quantitative and qualitative method, the researchers limited their literature review and data analysis to the writing errors by several scholars from various angles, excluding types of writing errors (i.e., interlingual and intralingual errors are the two main classifications of errors.) according to Brown (2000). Thirty-two (32) postgraduate students from different disciplines took part in this study. The major data collection tool was the students’ answer sheets from the elementary and pre-intermediate academic English curriculum at different English language levels (cutting edge). The current study seeks to address the type of writing errors and how frequently such writing errors occur in Kurdish EFL students’ writing. The researchers implemented process of coding for finding out writing errors, and tabulated their frequencies and percentages on bar charts. According to the findings of this study, the participants made fourteen different types of writing errors: grammar, punctuation, spelling, capitalization, literal translation, misuse of verbs, articles, unnecessary prepositions, misuse of pronouns, subject-verb agreement, misuse of prepositions, apostrophes, misuse of conjunctions and sing of wordiness. The findings of this study also revealed that the most common errors committed by the Kurdish learners were in grammar, punctuation, using of wordiness, spelling, and capitalization. Such results are important for EFL teachers because they encourage them to pay careful attention to their students’ writing errors and utilize them as pedagogical guidelines while designing activities.